Transduodenal resection for duodenal adenomas may be an underutilized tool – A single institution experience. Issue 4 (April 2022) - Logarajah, Shankar; Cho, Edward E.; Deleeuw, Peter; Osman, Houssam; Jeyarajah, D. Rohan
Abstract: Background: Duodenal adenomas are pre-malignant lesions. Transduodenal resection and pancreaticoduodenectomy remain the only two surgical options. The optimal surgical management remains controversial between these two strategies. Methods: A retrospective review was conducted to identify patients who underwent intervention for duodenal adenomas. Patient were stratified by type of procedure, pancreaticoduodenectomy or transduodenal resection, and their demographic data as well as perioperative outcomes were compared. Results: 26 patients underwent surgery for duodenal adenomas. 11 underwent a pancreaticoduodenectomy (PD) (42.3%) and 15 underwent a transduodenal resection (TDR) (57.7%). Median operative time, median estimated blood loss, and mean length of stay were longer in the PD vs TDR group. Two patients (13.3%) in the TDR group developed recurrent adenomas. Conclusion: Transduodenal resection should be considered in patients who are suspected to harbor benign duodenal tumors. Duodenal tumors with high grade dysplasia or invasive cancer should undergo an oncologic procedure. Endoscopic surveillance appears to be indicated after transduodenal resection. Abstract : Trandsuodenal Ampullectomy, Pancreaticoduodenectomy, Duodenal Adenoma.